VD_FINDINFO HC / 2010 / 96 vom 20. Oktober 2009 - VD Tribunal cantonal (2009)
FAUTE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 43 ch. 1 CP, 47 CP, 411 let. h CPP, 411 let. i CPP, 411 let. j CPP, 415 CPP